2012
DOI: 10.4103/0971-6580.97226
|View full text |Cite
|
Sign up to set email alerts
|

A case of acute pancreatitis with occupational exposure to organophosphorus compound

Abstract: Pesticides have contributed to dramatic increase in the quality and quantity in crop yields. Organophosphates are commonly used as insecticides in agriculture and are potent toxicants. Patients with organophosphorus poisoning may present with subclinical features of acute pancreatitis. Proper biochemical investigation and clinical correlation helps in diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In our cohort, there were pancreas, gallbladder, and liver disease cases among people with gastrointestinal problems. Studies have shown that people with pesticide poisoning may have subclinical signs of acute pancreatitis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, there were pancreas, gallbladder, and liver disease cases among people with gastrointestinal problems. Studies have shown that people with pesticide poisoning may have subclinical signs of acute pancreatitis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peradeniya OP poisoning scale 23 was used to assess severity or organophosphorus (OP) intoxication. Five common clinical manifestations of OP poisoning have been selected as parameters, each to be assessed on a 3-point scale varying from 0-2.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown that serum amylase above the normal range on the day of admission was related to the development of respiratory failure and the elevation of amylase level and predictive of subsequent respiratory failure [19][20] . Moreover, the elevated level of enzyme (hyperamylasaemia) is closely related to clinical severity and the presence of shock [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of organophosphorus poisoning is soaring due to easy availability in rural settings of developing countries where its use as pesticide is quite high [1] . Worldwide 3 million people are exposed each year with 300000 deaths attributed to them [2,3] .…”
Section: Introductionmentioning
confidence: 99%